Zmartwychwstanie umarłych jako jeden z dynamicznych wymiarów eschatologii - Dańczak, Andrzej (Verbum vitae, 2009)
The understanding of the bodily resurrection used to cause many problems during the history of the Christian theology. Also the catholic area was a scene of an interesting and wide discussion on the interpretation of the event, aiming at the elimination of many paradoxes present in eschatology. The debate unfortunately bas not bad a satisfactory result and bas not led the research to common conclusions. One of the possibilities of the solution is a wider and dynamic understanding of the resurrection, based on anthropological and biblical data. It requires a transposition of some traditional dimensions of the resurrection to other areas. Many aspects of the traditional contents of the theological meaning of the resurrection are in fact present already in the meaning of the event of death. It is there that a person experiences a total collapse of all vital forces but also a passage to another life. Thus the non-finality of death itself becomes part of human experience. Besides, the situation immediately after death means the entrance to the dimension of a personal fulfillment. Both themes belong to the theological meaning of the resurrection of the dead. Some other aspects of the resurrection are also present in the description of the Christian life and spring from the mystery of baptism whose meanings expressed in the language of the New Testament, among other things, in the resurrectional terms. Thus the resurrection cannot be seen as a static event of the end of times but rather as a dynamic event, some aspects of which are present already by means of the participation in the paschal mystery of Christ accessible by baptism, with later gradual and continuous progress and also with gradual fulfillment in the eschatological stadium where the material dimension of the creation must be included in order to make it possible to speak of the new creation.